2017
DOI: 10.1002/pc.24393
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of volcanic particle filled PLA/PBAT composites

Abstract: This study aims to investigate the influence of volcanic particles (VPs) incorporation on the thermal and mechanical properties of poly(lactic acid)/poly(butylene‐adipate‐co‐terephthalate) (PLA/PBAT) blends. Compounding was carried out using a twin‐screw microcompounder and injection molding at various PBAT contents such as 10, 20, 30, and 40 wt%. Optimum PBAT content was determined according to tensile results. 5, 10, 15, 20, and 25 wt% VP was incorporated into optimum PLA/PBAT blend. Thermal transitions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Typical composites are known to show a decreasing trend of elongation at break with increasing filler content . The increase in the elongation at break was not even of interest and was not reported previously . In the composite system of PLA–PBAT with fibers from the Amazon palm plant, the elongation at break was enhanced compared to that of the PLA–PBAT matrix, but the tensile strength and Young's modulus decreased significantly .…”
Section: Resultsmentioning
confidence: 74%
“…Typical composites are known to show a decreasing trend of elongation at break with increasing filler content . The increase in the elongation at break was not even of interest and was not reported previously . In the composite system of PLA–PBAT with fibers from the Amazon palm plant, the elongation at break was enhanced compared to that of the PLA–PBAT matrix, but the tensile strength and Young's modulus decreased significantly .…”
Section: Resultsmentioning
confidence: 74%
“…The phenyl ring constituting terephthalate unit is para‐doubly substituted, so a peak appears at 870 cm −1 is due to CH bending vibration. Moreover, a long chain band appears at 725 cm −1 is due to the presence of a large number of four consecutive methylene groups present in the PBAT polymer …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a long chain band appears at 725 cm −1 is due to the presence of a large number of four consecutive methylene groups present in the PBAT polymer. 17 TGA curve of the synthesized PBAT sample is displayed in Figure 4. The TG was measured between the temperature range from 30 to 900 C and the heating rate was maintained at 10 C/min.…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the thermal properties of the PLA/PBAT blends, Coban's team added volcanic rock particles (VPS) to the blends. The results show that when the VPS is added in an amount of 5 wt%, the thermal properties of the blends are at an optimum state (24). Li et al found that nanoclay can improve the interfacial adhesion between PLA and PBAT.…”
Section: Introductionmentioning
confidence: 99%